The Effectiveness of the National Logistic Ecosystem Program in Improving the Performance of the National Logistics System, Recovering the Investment Climate, and Increasing the Competitiveness of the National Economy - Pebriana Arimbhi; Dwi Agustina; Notika Rahmi (Jurnal Logistik Indonesia, 2021)
Logistics costs in Indonesia are one of the highest compared to 5 other ASEAN countries. Logistics performance is also said to have not improved in recent years. The National Logistic Ecosystem (NLE) program which is run by the Directorate General of Customs and Excise under the supervision of the Ministry of Finance is the government's real effort to improve national logistics performance, improve investment and increase the competitiveness of the national economy. The purpose of this research is to analyze the implementation, effectiveness and the impact of the application of the NLE program. This study uses a qualitative method with a descriptive approach. The results show that (1) of the six indicators of implementation assessment, there are two indicators that have not gone well, namely the attitude of the implementers and communication because there is still a planning agenda that will be carried out until 2024 and socialization is still being carried out (2) of the five appropriate indicators assessment of the effectiveness of the policy, only on target which cannot be seen thoroughly because there is still a process that must be passed in order to achieve the target. (3) The impact that has been felt is the realization of transparency of logistics service transactions, encouraging time and cost transparency and providing certainty of value added for every rupiah of costs incurred.